The quality of disclosure under IAS 38 in financial statements of entities listed on PSE - Michal Novák (European Financial and Accounting Journal, 2018)
There has been no recent examination of a disclosure of intangible assets under IFRS of entities listed on PSE. Hence, this article focuses on such an examination within financial statements reported for 2015 by entities listed on PSE and investigates whether these reports meet the minimum informational IFRS requirements. Adopted was the content analysis method, using a scoring system for the set of four questions which were answered (88 observations). The results revealed a poor level of the disclosure quality within the sample. Furthermore, our findings exposed a better level of disclosure for manufacturing companies relative to service companies, implicating a close linkage of disclosure compliance and the associated industry sector.
Keywords: M40; 650; Disclosure; IAS 38; IFRS; Intangible Assets